Precision attitude control of the Gravity Probe B satellite. (17th November 2015) - Conklin, J W; Adams, M; Bencze, W J; DeBra, D B; Green, G; Herman, L; Holmes, T; Muhlfelder, B; Parkinson, B W; Silbergleit, A S; Kirschenbaum, J
Abstract: The Gravity Probe B satellite used ultra-precise gyroscopes in low Earth orbit to compare the orientation of the local inertial reference frame with that of distant space in order to test predictions of general relativity. The experiment required that the Gravity Probe B spacecraft have milliarcsecond-level attitude knowledge for the science measurement, and milliarcsecond-level control to minimize classical torques acting on the science gyroscopes. The primary sensor was a custom Cassegrainian telescope, which measured the pitch and yaw angles of the experiment package with respect to a guide star. The spacecraft rolled uniformly about the direction to the guide star, and the roll angle was measured by star trackers. Attitude control was performed with sixteen proportional thrusters that used boil-off from the experiment's liquid Helium cryogen as propellant. This paper summarizes the attitude control system's design and on-orbit performance.